A Qualitative Study Of Classroom Interactiona - Dine, Radia; Menezla, Nadia (جامعة الوادي - University of Eloued, 2019)
Interaction is a vital construct in the social fabric of the classroom. The ability to instigate, maintain and foster such an endeavor is a necessity that researchers and practitioners are constantly seeking to promote. In this regard, developing a classroom interactional competence lies at the heart of fostering a dialogic pedagogy. The latter is a prerequisite in the learner-centered teaching/learning trend. Nevertheless, there have been scant studies that attempted to tackle the status quo of classroom interactional competence especially in the Algerian context on the grounds that classroom interactional competence is a byproduct of classroom ethos. Thus, the present research is attempt to shed light on classroom realms by investigating teachers’ attitudes and practices regarding classroom interactional competence in the Algerian context. To this end, three teachers fromthe university of Dr. Moulay Tahar (Saida) constituted the research subjects. Accordingly, a qualitative approach was opted for: a/classroom observation in which data was analyzed according to Walsh’s conversation analytical tool SETT (self-evaluation of teacher talk). Furthermore, a teachers’ interview was conducted with the selected teachers for the sake of obtaining a deeper understanding of their schemata and attitudes regarding classroom interactional competence. Resultsshowed a discrepancy between teachers’ professed attitudes and actual practices.
مقال
Keywords: classroom interactional competence, Self-Evaluation of Teacher Talk,Teacher based research, classroom ethos